Exploring the causality between ankylosing spondylitis and atrial fibrillation: A two-sample Mendelian randomization study - Chen, Shuhong; Luo, Xiqing; Zhao, Jiaoshi; Liang, Zhenguo; Gu, Jieruo (Frontiers in Genetics, 2022)
Objective: To study whether ankylosing spondylitis (AS) has a causal effect on the risk of atrial fibrillation (AF) using two-sample mendelian randomization (MR) analysis. Methods: Single nucleotide polymorphisms (SNPs) were selected as independent instrumental variables (IVs) from a GWAS study of AS. Summary data from a large-scale GWAS meta-analysis of AF was utilized as the outcome dataset. Inverse-variance weighted (IVW) model was used for the primary analysis. Multiple sensitivity and heterogeneity tests were conducted to confirm the robustness of the results. Results: In total, 18 SNPs were identified as IVs for MR analysis. Five MR methods consistently found that ankylosing spondylitis was not causally associated with atrial fibrillation (IVW: OR = 0.983 (0.894,1.080), P = 0.718; MR-Egger: OR = 1.190 (0.973,1.456), P = 0.109; Simple mode: OR = 0.888 (0.718,1.098), P = 0.287; Weighted mode: OR = 0.989 (0.854,1.147), P = 0.890; Weight median: OR = 0.963 (0.852,1.088), P = 0.545). Leave-one-out analysis supported the stability of MR results. Both the MR-Egger intercept and MR-PRESSO method revealed the absence of horizontal pleiotropy. Conclusion: The two-sample MR analysis did not support a causal relationship between AS and the risk of AF.